Secrecy and Concealment : Studies in the History of Mediterranean and Near Eastern Religions - Kippenberg, Hans G.; Stroumsa, Guy G. (Numen Book Series, 1995)
This volume deals with secrecy and concealment in the history of mediterranean religions as pattern of social interaction. Secrecy is a powerful means in establishing identity and interaction as G. Simmel has demonstrated. Using his approach the scholars of this volume describe and explain the practical meaning of concealment in two different religious systems: in Egyptian and Greek polytheism and in Jewish, Christian, Gnostic and Shi'i monotheisms. This point of view reveals that all these religions shaped social norms concerning public and private aspects of the human self.